We have a:b = 5:6 and b:c = 3: 7 We have to find (3c + 2a):a

Now a:b = 5:6 => a/b = 5/6

b:c = 3:7 => b/c = 3/7

(a/b)*(b/c) = (5/6)*(3/7)

=> a/c = 5/14

=> c/a = 14/5

(3c + 2a):a

=> 3c/a + 2a/a

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have a:b = 5:6 and b:c = 3: 7 We have to find (3c + 2a):a

Now a:b = 5:6 => a/b = 5/6

b:c = 3:7 => b/c = 3/7

(a/b)*(b/c) = (5/6)*(3/7)

=> a/c = 5/14

=> c/a = 14/5

(3c + 2a):a

=> 3c/a + 2a/a

=> 3(c/a) + 2

=> 3*14/5 + 2

=> 42/5 + 2

=> 52/5

**The value of (3c+2a):a = 52/5**